Surasadi Kadha (An Ayurvedic Decoction) - A Safe And Effective Formulation In Treatment Of COVID-19: A Single-Centered, Retrospective, Observational Study. - Charkha, Vd Varad; Charkha, Vd Shivprasad; Rao, K Shankar; Meena, Mohar Pal (International Research Journal of Ayurveda & Yoga, 2020)
COVID-19 has been declared as a pandemic and a global emergency. It has been spreading rapidly and has reached almost all the countries in the world. Confirmed cases are managed clinically but so far there have been no effective treatment or vaccine against it. Ayurveda has proved its potential in curing various kinds of diseases including viral infections. This study was aimed to observe and assess the safety and efficacy of an Ayurvedic decoction prepared from 10 selected Ayurvedic herbs on COVID-19 cases. 94 patients of COVID-19 in a government hospital who received the Ayurvedic decoction twice a day, in addition to the ongoing conventional treatment, were observed in this study. Data were collected through official sources such as case record forms, nursing record sheets, etc. These patients included people of all age group, were in different stage of the disease and having various co-morbidities. Conversion to mortality was set as primary outcome of this study. Symptomatic relief, changes in vital parameters and assessing safety of the decoction were set as secondary outcomes. Out of 94 patients, 65 were pre-symptomatic and 29 were symptomatic in condition. Men constituted 75.9% of symptomatic patients. The disease was more prevalent in middle age group (50-60) which had 1 of every 3 patients in this study. 29.8% patients were co-morbid. HTN followed by DM were observed to be the leading co-morbidities. Fever, breathlessness and cough were most commonly observed among symptomatic patients. 93 out of 94 patients eventually recovered and discharged with average 10 days of stay in the hospital. A single patient was transferred to the higher center. Not a single patient succumbed to the disease thus keeping the mortality rate nil. Rapid recovery rate was observed in patients having signs and symptoms. Those who were in pre-symptomatic condition did not develop any symptom during their stay in the hospital. The decoction was observed to be safe for patients of all age group and all conditions as no side effects or adverse drug reactions were seen. The study has shown that the Ayurvedic decoction as an additional intervention was safe and effective against COVID-19.